The Fundraising Digital di Lembaga Amil Zakat: Analisis Mendalam terhadap Metode dan Efektivitas Partisipasi Donatur - Sukendar, Egi Agustian Rahmat; Vidho, Ramadan (STAINI Press, 2025)
In Indonesia, the increase in internet penetration, which will reach 73.7% of the population or around 204.7 million people in 2022, has created great opportunities for the development of digital fundraising. LAZs such as BAZNAS and Dompet Dhuafa have utilized digital technology, which has been proven to increase fund collection. In 2023, BAZNAS reports that digital ZIS collection will reach IDR 47 trillion. Digital platforms such as Kitabisa and the use of e-wallets such as GoPay and OVO also support fundraising efficiency. However, challenges related to digital inequality and literacy still need to be overcome. Studies regarding the effectiveness of digital fundraising methods and their impact on increasing donor participation are also still limited, so further research is needed to identify the most effective strategies. This research aims to (1) find out and analyze the digital fundraising methods implemented by the Amil Zakat Institution. (2) To analyze the effectiveness of implementing the digital fundraising method in increasing donor participation at the Amil Zakat Institution. (3) To identify factors that influence the effectiveness of implementing digital fundraising methods in increasing donor participation at the Amil Zakat Institution. This research method uses a case study approach, where the researcher investigates a case or several cases in depth, involving collecting data that is rich in information. The case study was chosen because this research aims to carry out an in-depth analysis of the application of digital fundraising methods on the Amil Zakat Institution platform. With data collection techniques of observation, interviews and documentation.